DISTRICT HEATING OR DECENTRALIZED BOILERS IN RUSSIA - N. Lyubimova (Вестник университета)
The carried-out analysis showed that decrease in competitiveness of the centralized heat supply in Russia happened due to reduction of need for couple of industrial bodies, the increased wear, and imperfection of mechanisms of division of expenses between the electric power and heat at their cogeneration. In article it is noted that growth of number of participants and lack of uniform technical and investment policy of various sources of heat supply created an opportunity and need of formation of the local competitive markets of heat. The author proves that establishment of limit of a tariff for thermal energy with orientation to «an alternative boiler room» will promote overestimate of tariffs in the majority of regions of the country and discredits the idea of the competitive market of heat.